Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/aenm.202201131
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Plasma Exsolution from an A‐site Deficient Perovskite Oxide at Room Temperature

Abstract: and catalysis, capable of producing supported nanoparticles in a single synthesis step. [2][3][4][5][6][7] Exsolution was first observed on stoichiometric perovskite oxides where nanoparticles could be produced from transition metals present on the B-site of the perovskite oxide. This mechanism was initially referred to as solid-state recrystallization or self-regeneration. [8] Recently, however, the use of defect chemistry to synthesize the host oxides has revived the interest in exsolution because it allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 68 publications
(112 reference statements)
0
32
0
Order By: Relevance
“…Regarding irradiation, Kyriakou et al employed N 2 plasma treatment to facilitate exsolution, and found that the plasma-assisted exsolution can generate Ni nanoparticles that have up to ten times higher particle density compared to thermal chemical exsolution [37]. Recently, Khalid et al have leveraged argon plasma treatment to promote Ni exsolution out of La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 2.955 at room temperature [39]. Finally, in terms of thermal control of exsolution, Sun et al have utilized ultrafast thermal annealing (i.e.…”
Section: Tuning Defect Chemistry With External Stimuli To Control Exs...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding irradiation, Kyriakou et al employed N 2 plasma treatment to facilitate exsolution, and found that the plasma-assisted exsolution can generate Ni nanoparticles that have up to ten times higher particle density compared to thermal chemical exsolution [37]. Recently, Khalid et al have leveraged argon plasma treatment to promote Ni exsolution out of La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 2.955 at room temperature [39]. Finally, in terms of thermal control of exsolution, Sun et al have utilized ultrafast thermal annealing (i.e.…”
Section: Tuning Defect Chemistry With External Stimuli To Control Exs...mentioning
confidence: 99%
“…Additionally, employing extrinsic techniques to control the crystal faces on the surface i.e. particle shape would make possible the design of highly active, selective and tailored materials [11,39,186], enabling a functional diversity that will allow for more efficient CL processes. As mentioned above, preparation method plays a key role in the nano and microstructure of these materials and modification of the current synthesis methods would impact on the microstructure of the backbone matrixes.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…In addition to plasma discharge, the activated N-containing species also participated in stripping oxygen from the perovskite. Khalid et al 105 found that in low-temperature plasma under an argon atmosphere, the perovskite La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 2.955 with A-site deficiency achieved large particle densities with a diameter range of 19–22 nm at room temperature within 15 min. The schematic illustration of the plasma-driven exsolution of Ni nanoparticles is shown in Fig.…”
Section: New Implications In Exsolutionmentioning
confidence: 99%
“…2,3 Since ultrafine (e.g., sub-5 nm) 16,17 and multi-element 18 nanoparticles can have higher catalytic activities, it is desirable to exsolve nanoparticles with tunable composition (multicomponent) and with tunable (reduced) size. Researchers have tried various methods, such as doping, 19,20 plasma treatment, 21,22 and electrochemistry 23,24 (see Table S1, ESI † for a more comprehensive summary) to tailor exsolution. While significant progress has been made, most strategies proposed thus far still rely on choosing a specific host oxide composition for metal exsolution.…”
Section: Introductionmentioning
confidence: 99%